Armenia Economic Report, October 2013 : Stronger Structural Reforms Needed to Offset Macroeconomic Risks - World Bank (World Bank, Washington, DC, 2017)
This economic report records the economic activities of Armenia for the year 2013. A steep decline in construction caused economic growth to weaken to 0.6 percent in the second quarter of 2013 (year-on-year) from 7.5 percent in the first quarter and 7.2 percent in 2012 as a whole. Developments of the current account were more favorable than expected earlier. The volume of metal exports rose substantially, more than offsetting lower international prices for copper and remittances remained high despite the slowdown of economic growth in Russia. For a third year in a row, fiscal policy is likely to be tighter because of lower than budgeted capital spending. This outcome reflects delays in the North-South corridor infrastructure project. With continued sluggish growth expected in Armenia’s main trading partners, including Russia and the European Union (EU), we project growth of about 4–5 percent a year over the medium term. Armenia’s authorities recognize the need to improve the business environment and competitiveness. The government’s medium-term reform agenda, supported by a new Development Policy Operation from the World Bank, reflects these priorities. It includes critical business climate and public administration reforms, aimed at strengthening competitiveness and public sector efficiency. These are expected to contribute to job creation through reducing the costs of doing business for firms, expanding access to credit to Small and medium enterprises (SMEs), and increasing opportunities for employment and job creation through increased trade and connectivity within and outside Armenian borders.